2013
DOI: 10.4161/hv.22377
|View full text |Cite
|
Sign up to set email alerts
|

Safety of post-exposure rabies prophylaxis during pregnancy: A follow-up study from Guangzhou, China

Abstract: This study aimed to assess the safety profile of post-exposure prophylaxis (PEP) for rabies in pregnant women. All of the subjects received the Essen vaccination regimen. Systemic and local reactions were monitored within 72 hours following the immunization, and the subjects were followed until six months after delivery. No moderate or severe adverse effects occurred in any subject following the vaccination. Among the 72 subjects in this follow-up study, four had voluntary abortions, one subject had an acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The majority of intervention studies were conducted in Asia (China, India, Philippines, Thailand) [7,9,10, and eight studies in Europe (Austria, Croatia, Czech Republic, Germany, Lithuania, Serbia) [8,[41][42][43][44][45][46][47]. All the observational studies were conducted in Asian countries [19,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of intervention studies were conducted in Asia (China, India, Philippines, Thailand) [7,9,10, and eight studies in Europe (Austria, Croatia, Czech Republic, Germany, Lithuania, Serbia) [8,[41][42][43][44][45][46][47]. All the observational studies were conducted in Asian countries [19,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]].…”
Section: Search Resultsmentioning
confidence: 99%
“…The AEs were local pain (22.5%), fatigue (18.3%), fever (2.8%), local erythema (1.4%), and headache (1.4%). No miscarriages, stillbirths, or fetal malformations were reported, and birth weights were within ranges considered normal for neonates in China [49].…”
Section: Special Populationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Today's vaccine is much better tolerated than earlier preparations. Case reports and series regarding the active and/or passive immunization with more than 330 pregnant women demonstrate no adverse effects (Huang 2013, Toovey 2007, Chutivongse 1995. Maternal antibodies appear to cross the placenta.…”
Section: Rabies Vaccinationmentioning
confidence: 92%
“…Yet, no publications included in this review detailed how perceived safety concerns among participants were addressed during enrollment, and only one study included in this review discussed how safety concerns affected study participation. In a prospective cohort of pregnant women exposed to rabies, study investigators reported that several participants withdrew from the study, or refused post-exposure prophylaxis due to perceived safety concerns 20 . However, the need for further health education to eliminate perceived safety concerns was expressed 20 …”
Section: Spectrum Of Ethical Issues In Maternal Immunizationmentioning
confidence: 99%